And (a+b)(a−b) means (a+b) multiplied by (a−b). We usage that a lot here!

## Special Binomial Products

So as soon as we multiply binomials we acquire ... Binomial Products!

And we will certainly look in ~ three special cases of multiply binomials ... So they are Special Binomial Products.

You are watching: How to find the product of binomials

## 1. Multiply a Binomial through Itself

What happens once we square a binomial (in other words, main point it by itself) .. ?

(a+b)2 = (a+b)(a+b) = ... ?

The result:

(a+b)2 = a2 + 2ab + b2

This illustration mirrors why that works: ## 2. Subtract times Subtract

And what happens when we square a binomial v a minus inside?

(a−b)2 = (a−b)(a−b) = ... ?

The result:

(a−b)2 = a2 − 2ab + b2

If you desire to watch why, climate look at how the (a−b)2 square is equal to the big a2 square minus the other rectangles: (a−b)2 = a2 − 2b(a−b) − b2 = a2 − 2ab + 2b2 − b2 = a2 − 2ab + b2

And then there is one an ext special instance ... What around (a+b) time (a−b) ?

(a+b)(a−b) = ... ?

The result:

(a+b)(a−b) = a2 − b2

That to be interesting! It finished up really simple.

And that is referred to as the "difference of two squares" (the 2 squares space a2 and also b2).

This illustration reflects why it works: a2 − b2 is same to (a+b)(a−b)

Note: (a−b) could be first and (a+b) second:

(a−b)(a+b) = a2 − b2

## The 3 Cases

Here room the three outcomes we just got:

 (a+b)2 = a2 + 2ab + b2 } the "perfect square trinomials" (a−b)2 = a2 − 2ab + b2 (a+b)(a−b) = a2 − b2 the "difference that squares"

Remember those patterns, castle will conserve you time and aid you solve many algebra puzzles.

See more: What Pokemon Evolve From A Moon Stone And Item Locations (Walkthroughs)

## Using Them

So much we have actually just used "a" and "b", yet they could be anything.

### Example: (y+1)2

We can use the (a+b)2 situation where "a" is y, and also "b" is 1:

(y+1)2 = (y)2 + 2(y)(1) + (1)2 = y2 + 2y + 1

### Example: (3x−4)2

We have the right to use the (a-b)2 case where "a" is 3x, and "b" is 4:

(3x−4)2 = (3x)2 − 2(3x)(4) + (4)2 = 9x2 − 24x + 16

### Example: (4y+2)(4y−2)

We recognize the result is the difference of two squares, because:

(a+b)(a−b) = a2 − b2

so:

(4y+2)(4y−2) = (4y)2 − (2)2 = 16y2 − 4

Sometimes we can see the sample of the answer:

### Example: i beg your pardon binomials multiply to gain 4x2 − 9

Hmmm... Is the the difference of two squares?

Yes!

4x2 is (2x)2, and 9 is (3)2, so us have:

4x2 − 9 = (2x)2 − (3)2

And that can be created by the distinction of squares formula:

(a+b)(a−b) = a2 − b2

Like this ("a" is 2x, and "b" is 3):

(2x+3)(2x−3) = (2x)2 − (3)2 = 4x2 − 9

So the price is that we have the right to multiply (2x+3) and (2x−3) to acquire 4x2 − 9